Temas e teimas : o discurso feminino e feminista de Marina Colasanti - Monteiro, Maria Aparecida de Araújo (2009)
It shows the reading of the female identity development based on Marina Colasanti’s writing. Through this author, the writing performance is analyzed on different textual genres in order to build a female voice to find out its place on the text and in the history. It proposes a view over the female movement and the influence of this social movement on the literature on a broad perspective and specifically on Marina Colasanti’s production. It aims to analyze how the female movement decreasing happened and its gradual substitution on the genre matters.